Implementation Of Traditional Risk Management As Loss Prevention In Coconut Production Results - Hadi, Muhammad Nur (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2022)
In Kalimantan, coconut is one of the main commodities which is a source of community income. This happened, because the characteristics of Kalimantan's soil are very suitable for coconut plantations, so that most of the people have coconut gardens. However, in the process of raising it to make money, there are many risks. These conditions encourage farmers to be able to find solutions, so that coconut products remain a source of income. This study aims to analyze the risks in coconut plantations, which have an impact on selling value/price, economic value, income, to welfare. The research method used is quantitative with regression analysis as a causal estimation tool between variables. The research sample was taken randomly from 150 coconut farmers in the Kalimantan region. The results showed that the risk in the coconut industry is the reduction in the number of trees due to the conversion of mining and other plantations. Then another risk is operational costs that are not balanced with the selling price. This condition is often complained of by farmers, and because they do not have the ability to overcome it, farmers can only reduce the number of production activities, starting from maintenance to distribution.